Effect of dairy manure to switchgrass co-digestion ratio on methane production and the bacterial community in batch anaerobic digestion. (1st August 2015) - Zheng, Zehui; Liu, Jinhuan; Yuan, Xufeng; Wang, Xiaofen; Zhu, Wanbin; Yang, Fuyu; Cui, Zongjun
Highlights: Switchgrass is a suitable substrate for biogas production but requires buffering. Dairy manure as a co-substrate increases the stability of anaerobic digestion. The highest methane yield was achieved with a 2:2 ratio of manure to switchgrass. Co-digestion doubled the volumetric productivity of methane in batch tests. The bacterial community structure varies greatly with different co-substrate ratios. Abstract: The methane yield and microbial community resulting from co-digestion of dairy manure and switchgrass at different mixing ratios [4:0, 3:1, 2:2, 1:3, and 0:4 based on total solids (TS) content] were evaluated. The results indicated that switchgrass is an excellent feedstock for biogas production when co-digested with dairy manure. Mono-digestion of a high dose (>4% TS) of switchgrass led to volatile fatty acid accumulation and process failure, whereas co-digestion of switchgrass and dairy manure could increase the buffering capacity and improve the fermentation efficiency. The optimal mixture ratio of dairy manure and switchgrass was 2:2, with a methane yield that was 39% higher than that obtained by digestion of the individual substrates. The added amount of 8% TS at the 2:2 ratio achieved the highest methane yield of 158.6 mL/g VS, which corresponded to a 1.3-fold increase in the volumetric productivity of methane compared to mono-digestion of 4% TS switchgrass. Quantitative polymerase chain reaction and clone library analyses showed significant differences in the bacterial community resulting from the different co-substrate ratios. Planctomycetes (28%), Chloroflexi (24%), and Bacteroidetes (24%) were the dominant phyla in digesters with a co-substrate ratio of 2:2.